P132: Trampoline park safety perceptions of caregivers of patients presenting to the paediatric emergency department in London, Ontario. (May 2019) - Lynch, T.; Van de Kleut, C.; Van Aarsen, K.
Abstract : Introduction : Trampoline injuries are frequent complaints of children presenting to paediatric emergency departments (PED) in Canada. The medical community has recognized the danger of recreational trampoline use, with the Canadian Paediatric Society (CPS) formally recommending against their use. A new type of trampoline recreation has recently emerged in the form of trampoline parks. Trampoline parks are dangerous, with similar rates of injury as backyard trampolines, and an increased likelihood of injuries warranting hospital admission. No current Canadian governmental or industry regulations exist for trampoline parks. This study aimed to determine the public perspective of trampoline park safety in order to provide a basis for addressing the current lack of safety recommendations around trampoline parks.Methods : Parents/caregivers of children seeking care in the PED were approached to participate in a survey regarding trampoline safety. Parents/caregivers of patients with severe injury/illness were excluded. Survey questions included demographics, safety perceptions of both home trampolines and trampoline parks, as well as awareness of the CPS statement regarding trampoline use. The survey was completed in the Research Electronic Data Capture System.Results : To date, 68 participants have completed the survey. 66% of participants (45/68) were aware of the new trampoline parks recently opening in the community. 31/68 (46%) of participants had allowed their child to visit a trampoline park. A comparison of the perception of the relative safety of trampoline parks found that 31% of participants (21/67) considered home trampolines "safe/very safe" while 39% of participants (26/66) considered trampoline parks "safe/very safe." The median [IQR] age at which participants thought children could safely play at trampoline parks was 10 [3-15]. 43% of participants (29/67) thought the current CPS statement about backyard trampolines should apply to trampoline parks, and 93% of participants (62/67) thought the Ontario government should institute mandatory standards for trampoline parks.Conclusion : Trampoline parks are a significant emerging source of paediatric injury. Trends in preliminary data suggest that participants consider trampoline parks to be safer than backyard trampolines, and perceive that young children can safely participate in trampoline park activities. Should final survey data analysis support these trends, a call for adjustment of CPS guidelines and public policy should proceed.